Application of Isothermal Signal Amplification Technique in the Etiological Diagnosis of Gonorrhea and Drug Resistance Gene Detection. (1st July 2022) - Chen, Wei; Zhang, Jinling; Li, Dongsheng; Wang, Yue
Abstract : Background: Isothermal signal amplification technique is developed based on the rolling ring amplification mechanism of cyclic DNA molecules in nature. This technique plays an extremely beneficial role in gonorrhea pathogen identification and drug resistance gene detection. Aims : This study analyzes the isothermal signal amplification techniques in the etiological diagnosis of gonorrhea and drug resistance gene detection. Materials and Methods : Urethral, cervical secretion, or prostatic fluid samples from 322 cases of gonorrhea collected from January 2018 to December 2021 at the STD clinic of our hospital dermatology department were selected for direct smear examination and gonococcal culture examination; DNA was extracted from urethral, cervical secretion, or prostatic fluid samples and then used for pathogen identification by SAT assay and rolling loop nucleic acid amplification technique, smear examination and pathogen culture examination methods, SAT assay, and isothermal signal amplification technique for comparative sensitivity and specificity analysis. Results : The highest rate of gonorrhea positivity was for the urine rolling loop nucleic acid amplification technique, followed by the swab rolling loop nucleic acid amplification technique, and the lowest rate of gonorrhea positivity was for the urine SAT test. The difference in the positivity rate between the two urine testing methods was statistically significant (P < 0.05 ). The highest sensitivity of the urine rolling loop nucleic acid amplification technique method for the detection of gonorrhea pathogens and the lowest sensitivity of the urine SAT method were statistically significant (P < 0.01 ). The differences in sensitivity and specificity between the swab rolling loop nucleic acid amplification technique and the swab SAT method were not statistically significant (P > 0.05 ). ROC curves were plotted based on sensitivity and specificity, with swab SAT assay (A U C = 0.998 ) > rolling loop nucleic acid amplification technique (A U C = 0.981 ). Comparing the negative rates of urine and swab rolling loop nucleic acid amplification technique and urine SAT assay, the differences were not statistically significant (P > 0.05 ). Conclusion : The isothermal signal amplification technique improves the shortcomings of gonorrhea pathogen identification means and drug resistance gene detection methods, with good detection sensitivity and specificity, simple operation, low price, and easy promotion, which has obvious advantages in clinical applications and epidemiological studies.